Public perception of community pharmacists in South Africa: a preliminary study - Suzanne Bornman; Ilse Truter; Daniel JL Venter (AOSIS, 2006)
This survey forms part of a study undertaken to identify and quantify the community pharmacist's involvement in the use of non-prescription/over-the-counter (OTC) medicine/self-medication in community pharmacies throughout South Africa. Opsomming Hierdie opname vorm deel van 'n studie wat onderneem word om die gemeenskapsapteker se betrokkenheid in die gebruik van nie-voorskrif/oor-die-toonbank medikasie/ selfmedikasie in gemeenskapsapteke in Suid Afrika te identifiseer en te kwantifiseer. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.